2011
DOI: 10.1016/j.cub.2011.03.033
|View full text |Cite
|
Sign up to set email alerts
|

A Chiton Uses Aragonite Lenses to Form Images

Abstract: Hundreds of ocelli are embedded in the dorsal shell plates of certain chitons. These ocelli each contain a pigment layer, retina, and lens, but it is unknown whether they provide chitons with spatial vision. It is also unclear whether chiton lenses are made from proteins, like nearly all biological lenses, or from some other material. Electron probe X-ray microanalysis and X-ray diffraction revealed that the chiton Acanthopleura granulata has the first aragonite lenses ever discovered. We found that these lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 24 publications
(32 reference statements)
3
67
0
Order By: Relevance
“…S7). Since aragonite is a pseudo-uniaxial crystal, the non-normal orientation of the c-axes should generate double refraction, which is consistent with observations that the lenses are birefringent when viewed with polarized light (17,18). In addition, EBSD showed that the lenses have an average grain size of roughly 10 µm, which is approximately an order of magnitude greater than that of the surrounding granular microstructure ( fig.…”
supporting
confidence: 72%
See 4 more Smart Citations
“…S7). Since aragonite is a pseudo-uniaxial crystal, the non-normal orientation of the c-axes should generate double refraction, which is consistent with observations that the lenses are birefringent when viewed with polarized light (17,18). In addition, EBSD showed that the lenses have an average grain size of roughly 10 µm, which is approximately an order of magnitude greater than that of the surrounding granular microstructure ( fig.…”
supporting
confidence: 72%
“…Unlike the few other eyes known to contain lenses made of calcium carbonate, such as those of trilobites (19,20), the eyes of chitons are integrated within and dispersed across their entire dorsal shell surface instead of being localized to a particular region of the body. Although the calcitic lenses of brittlestars are also dispersed across their dorsal arm plates (4), it is unclear whether or not they enable spatial vision in a fashion similar to the lenses of chitons (18). Here we show that the chiton A. granulata is able to tailor the local geometry, crystallography, and interfaces of aragonite to achieve a multifunctional armor.…”
mentioning
confidence: 74%
See 3 more Smart Citations